Evaluating PowerPoint Presentations: A Retrospective Study Examining Educational Barriers and Strategies. Issue 1 (January 2016) - Nowak, Marian K.; Speakman, Elizabeth; Sayers, Patricia
Abstract: AIM: To assess faculty adherence to best practices for PowerPoint presentations in nursing school curricula. BACKGROUND: It is important to examine current educational methods and identify best educational practices that contribute to a high quality nursing curriculum. METHOD: A retrospective study approach was used. Data were collected from 1, 735 slide presentations from five universities. PowerPoint ® presentations were compared to a nine-point standardized scoring criterion for quality. RESULTS: Findings provide evidence that indicated classroom presentations often fall short of providing best educational practices. CONCLUSION: These findings can lead to greater faculty understanding of best practices and provide strategies to reinvent educational methods that engage students.